THE INFLUENCE OF HALAL DESTINATION ATTRIBUTES IN WEST SUMATERA ON MUSLIM TOURISTS - Nur Aulia Noviyani; Ririn Tri Ratnasari (Universitas Airlangga, 2021)
ABSTRAKSumatera Barat telah dinobatkan sebagai destinasi wisata halal terbaik di dunia karena memiliki halal destination attributes yang sangat ramah terhadap wisatawan Muslim. Dalam penelitian ini akan dijelaskan bagaimana pengaruh halal destination attributes di Sumatera Barat terhadap experience quality dan destination satisfaction dari wisatawan Muslim. Penelitian ini menggunakan pendekatan kuantitatif yang diuji dengan teknik analisis jalur dan diolah menggunakan program AMOS. Hasil penelitian menemukan bahwa halal destination attributes di Sumatera Barat berpengaruh postif signifikan terhadap experience quality wisatawan Muslim dan destination satisfaction. Kemudian, ditemukan juga pengaruh positif signifikan antara experience quality terhadap destination satisfaction. Dengan mengoptimalkan halal destination attributes di Sumatera Barat, maka akan meningkatkan experience quality dan destination satisfaction dari wisatawan Muslim yang berkunjung. Hal ini menjadi penting karena akan berdampak terhadap jumlah kunjungan wisatawan Muslim ke Sumatera Barat.Kata Kunci: Destinasi Wisata Halal, Halal Destination Attributes, Experience Quality, Destination Satisfaction, Wisatawan Muslim. ABSTRACTWest Sumatera has been named the best halal tourist destination in the world because it has halal destination attributes that are very friendly to Muslim tourists. In this study, it will be explained how the influence of halal destination attributes in West Sumatera on experience quality and destination satisfaction of Muslim tourists. This study uses a quantitative approach which is tested with path analysis techniques and processed using the AMOS program. The results of the study found that halal destination attributes in West Sumatera have a significant positive effect on the experience quality of Muslim tourists and destination satisfaction. Then, it was also found that experience quality has a significant positive effect on destination satisfaction. By optimizing the halal destination attributes in West Sumatera, it will increase the experience quality and destination satisfaction of visiting Muslim tourists. This is important because it will have an impact on the number of Muslim tourists visiting West Sumatera.Keywords: Halal Travel Destinations, Halal Destination Attributes, Experience Quality, Destination Satisfaction, Muslim Tourists.DAFTAR PUSTAKAAl-Ansi, A., & Han, H (2019). Role of halal-friendly destination performances, value, satisfaction, and trust in generating destination image and loyalty. Journal of Destination Marketing & Management, 13(September 2019), 51-60. https://doi.org/10.1016/j.jdmm.2019.05.007Albayrak, T., & Caber, M. (2013). The symmetric dan asymmetric influences of destinaton attributes on overall visitor satisfaction. Current Issues in Tourism, 16(2), 149-166. https://doi.org/10.1080/13683500.2012.682978Battour, M. and Ismail, M. N. dan Battor, M. (2011). The impact of destination attributes on moslem tourist's choice. International Journal of Tourism Research, 13(6), 527-540. https://doi.org/10.1002/jtr.824Battour, M., Battor, M., & Bhatti, M. A. (2014). Islamic attributes of destination: Construct development and measurement validation, and their impact on tourist satisfaction. International Journal of Tourism Research, 16(6), 556-564.Battour, M., & Ismail, M. N. (2015). Halal tourism: Concepts, practises, challenges and future. Tourism Management Perspectives, 19(July 2016), 150-154. https://doi.org/10.1016/j.tmp.2015.12.008Caber, M., & Albayrak, T. (2016). Push or pull? Identifying rock climbing tourists' motivations. Tourism Management, 55, 74-84.Cetin, G., & Bilgihan, A. (2016). Components of cultural tourists' experiences in destinations. Current Issues in Tourism, 19(2), 137-154.Chang, T.-Y., & Horng, S.-C. (2010). Conceptualizing and measuring experience quality: The customer's perspective. Service Industries Journal, 30(14), 2401-2419.Chen, C.-F., & Chen, S.-F. (2010). Experience quality, perceived value, satisfaction and behavioral intentions for heritage tourists. Tourism Management, 31(1), 29-35.Chiu, W., & Zeng, S. (2016). Determinants of Chinese tourists' loyalty to Korea: A comparison of film and non-film tourist perceptions. International Journal of Social Science dan Humanity, 6(9), 667-671.Cong, L. C. (2016). A formative model of the relationship between destination quality, tourist satisfaction and intentional loyalty: an empirical test in Vietnam. Journal of Hospitality and Tourism Management, 26, 50-62.Departemen Agama Republik Indonesia. (2020). Terjemahan Al-Qur'an. Diakses dari https://quran.kemenag.go.id/Dewi, I. J. (2011). Implementasi dan implikasi kelembagaan pemasaran pariwisata yang bertanggung jawab (Responsible tourism marketing). Yogyakarta: Kementerian Kebudayaan dan Pariwisata Republik Indonesia.Dinas Pariwisata Provinsi Sumatera Barat. (2019). Statistik pariwisata Sumatera Barat (SPSB). Padang: Dinas Pariwisata Provinsi Sumatera Barat.Dobrota, M., Nikodijevic, A., & Mihailovic, D. (2012). Influences of the customer experience on satisfaction with mobile phones. Journal of Enginerering Management and Competitiveness, 2(2), 69-75.Ekanayake, I. A., & Gnanapala, A. C. (2016). Travel experience and behavioral intention of the tourist: A study on Eastern Province of Sri Lanka. Tourism, Leisure and Global Change, 3, 50-61.Fahham, A. M. (2017). Tantangan pengembangan wisata halal di Nusa Tenggara Barat. Aspirasi, 8(1), 65-79.Fu, X., Yi, X., Okumus, F., & Jin, W. (2019). Linking the internal mechanism of exhibition attachment to exhibition satisfaction: A comparison of first-time dan repeat attendees. Tourism Management, 72, 92-104.Hammuri, G., & Eseynel, I. (2017). The analysis of hoteliers attitude towards the establishment of Islamic hospitality policies: North Cyprus. Saudi Journal of Homanities and Social Sciences, 2(2), 124-131.Han, H., Al-Ansi, A., Olya, H. G. T., & Kim, W. (2019). Exploring halal-friendly destination attributes in South Korea: Perceptions and behaviors of muslim travelers toward a non-muslim destination. Tourism Management, 71, 151-164.Hassan, Z. (2015). Factors affecting muslim tourists choice of halal concept hotels and satisfaction in Malaysia: Moderating effect of religious devotedness. International Journal of Accounting & Business Management, 3(2), 133-144.Hayati, A., & Ratnasari, R. T. (2020). Factors affecting muslim consumer decisions on choosing Islamic hotel. Hamdard Islamicus, 43(S.2), 619-638.Henderson, J. C. (2016). Halal food, certification and halal tourism: Insight from Malaysia and Singapore. Tourism Management Perspective, 30, 1-5.Jaelani, A. (2017). Industri wisata halal di Indonesia: Potensi dan prospek. Mpra, 76237, 1-20.Kartajaya, H., & Sula, M. S. (2006). Syariah marketing. Bandung: PT Mizan Pustaka.Kim, J.-H. (2014). The antecedents of memorable tourism experiences: The development of a scale to measure the destination attributes associated with memorable experiences. Tourism Management, 44, 34-45.Komite Nasional Ekonomi dan Keuangan Syariah (KNEKS). (2020). Laporan perkembangan pariwisata ramah muslim daerah 2019-2020. Jakarta: Direktorat Infrastruktur Ekosistem Syariah.Lemke, F., Clark, M., & Wilson, H. (2010). Customer experience quality: An exploration in business and consumer contexts using repertory grid technique. Journal of the Academy of Marketing Science, 39(6), 846-869.Mardianto, M. F. F., Cahyono, E. F., Syarifah, L., & Andriani, P. (2019). Prediction of the number of foreign tourist arrival in Indonesia halal tourism entrance using simultaneously fourier series estimator. KnE Social Sciences, 1093-1104.Mill, R. C., & Morrison, A. M. (2013). The tourism system. Australia: Kendall Hunt.Moon, H., & Han, H. (2018). Destination attributes inﬂuencing Chinese travelers' perceptions of experience quality and intentions for island tourism: A case of Jeju island. Tourism Management Perspectives, 28, 71-82.Rahman, M. K. (2014). Motivating factors of Islamic tourist's destination loyalty: An empirical investigation in Malaysia. Journal of Tourism and Hospitality Management, 2(1), 63-77.Rahman, M., Moghavvemi, S., Thirumoorthi, T., & Rahman, M. K. (2020). The impact of tourists’ perceptions on halal tourism destination: A structural model analysis. Tourism Review, 75(3), 575-594.Ramseook-Munhurrun, P., Seebaluck, V. N., & Naidoo, P. (2015). Examining the structural relationships of destination image, perceived value, tourist satisfaction and loyalty: Case of Mauritus. Procedia-Social dan Behavioral Sciences, 175, 252-259.Ratnasari, R. T., Gunawan, S., Mawardi, I., & Kirana, K. C. (2020). Emotional experience on behavioral intention for halal tourism. Journal of Islamic Marketing, 12(4), 864-881. https://doi.org/10.1108/JIMA-12-2019-0256Rozalinda, N., & Ramadhan, S. (2019). Industri wisata halal di Sumatera Barat: Potensi, peluang dan tantangan. Maqdis: Jurnal Kajian Ekonomi Islam, 4(1), 46-56.Schlesinger, W., Cervera-Taulet, A., & Perez-Cabanero, C. (2020). Exploring the links between destination attributes, quality of service experience and loyalty in emerging mediterranean destinations. Tourism Management Perspectives, 35, 100699.Sdanjojo, N. (2011). Metode analisis jalur (Path snalysis) dan aplikasinya. Jakarta: Pustaka Sinar Harapan.Sedianingsih, Ratnasari, R. T., Prasetyo, A., & Hendarjatno. (2019). Antecedents of recommendation and repurchase intention on medical tourism. Opcion, 35(23), 1277-1300.Shaykh-Baygloo, R. (2021). Foreign tourists' experience: The tri-partite relationship among sense of place toward destination city, tourism attractions and tourists' overall satisfaction - evidence from Shiraz, Iran. Journal of Destination Marketing & Management, 19, 100518.Siyoto, S., & Sodik, M. A. (2015). Dasar metodologi penelitian. Yogyakarta: Literasi Media Publishing.Sugiyono, P. D. (2016). Metode penelitian kuantitatif, kualitatif dan R&D. Bandung: Alfabeta.Suwantoro, G. (2004). Dasar-dasar pariwisata. Yogyakarta: Dani.Truong, T. H., & King, B. (2009). An evaluation of satisfaction levels among Chinese tourist in Vietnam. International Journal of Tourism Research, 11(6), 521-535.Wu, H.-C., & Li, T. (2017). A study of experiential quality, perceived value, heritage image, experiential satisfaction, and behavioral intentions for heritage tourists. Journal of Hospitality & Tourism Research, 41(8), 904-944.Wu, H.-C., Cheng, C.-C., & Ai, C.-H. (2018). A study of experiential quality, experiential value, trust, corporate reputation, experiential satisfaction and behavioral intentions for cruise tourists: The case of Hong Kong. Tourism Management, 66, 200-220.Yuliviona, R., Alias, Z., & Abdullah, M. (2019). The effect of Islamic attributes of destination, experiental values on revisit intention among muslim tourists: Model testing on the mediating role of satisfaction. Journal of Environmental Treatment Techniques, 7(4), 768-773.Zabkar, V., Brencic, M. M., M., & Dmitrovic, T. (2010). Modelling perceived quality, visitor satisfaction and behavioural intention at the destination level. Tourism Management, 31(4), 537-546.Zaki, I., Hamida, G., & Cahyono, E. F. (2020). Potentials of implementation of sharia principles in the tourism sector of Batu city, East Java. Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 4(1), 96-111.